Millennial‐scale changes in bottom water temperature and water mass exchange through the Fram Strait 79ºN, 63–13 ka - El Bani Altuna, Naima; Ezat, Mohamed; Greaves, M.; Rasmussen, Tine Lander (Paleoceanography and Paleoclimatology, 2020)
The Svalbard margin, in the eastern Fram Strait with its high sediment accumulation, form a key area for the reconstruction of water mass and heat exchange between the North Atlantic and Arctic Ocean in relation to abrupt climate changes as seen in glacial Greenland Interstadial and Greenland Stadial (GI‐GS) events. Here, we present a bottom water temperature (BWT) record from the northern Nordic Seas (79°N) at 1273 m water depth based on benthic foraminiferal Mg/Ca. The BWT reconstructions, combined with benthic foraminiferal stable isotopes, benthic foraminiferal fauna compositions and ice rafted debris (IRD), reveal at least two distinctive scenarios for the GI‐GS events during the last glacial period (13–63 ka). During GIs, conditions were similar to modern with high productivity, low BWT and deep convection. During GS6, GS8 and GS15 and during Heinrich Stadials (HSs), BWT increased up to 5±1°C generally concomitant with low planktic and benthic δ18O. Our results suggest, that during some GSs and HSs, deep water generation was reduced, allowing the subsurface Atlantic water to thicken and deepen down to at least the core site depth. A strong halocline during HSs and GSs prevented heat release from the subsurface Atlantic water, which we can now trace from 45ºN in the North Atlantic to the Arctic Ocean >79ºN. Surfacing of the salty Atlantic subsurface water pre‐conditioned the Nordic seas for convection. Release of the subsurface heat from this vast reservoir must have contributed to the large and abrupt atmospheric warmings at the start of Greenland interstadials.